MEWUJUDKAN PEMERINTAHAN EFEKTIF DALAM SISTEM MULTIPARTAI - Benyamin Tungga (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2020)
Multiparty system is a product of a pluralist or plural society structure, both in terms of religiosity, ethnicity, and socio-economic. The party system should support the formation of a strong and clean government system and increase the effectiveness of government or the level of representation, but in reality each party is more concerned with their respective interests. The multiparty system in a presidential system in Indonesia makes the government instability in Indonesia. This mix is ​​believed to tend to give birth to minority presidents and divided governments. There are four important things that influence the multiparty system on presidential systems in Indonesia. First, the multiparty system affects the fragility of coalition ties in the DPR. Second, the excessive control of the DPR disrupts the effectiveness of government. Third, the multiparty system affects the power of the vice president which is more dominant in the government and Fourth, the president's prerogative rights are reduced.